Financial literacy among working adults: The case of Saudi Arabia - Mansour Saleh Albarrak; Sara Ali Alokley; Yasmeen Ansari (Quantitative Finance and Economics)
We aimed to evaluate the financial literacy of working adults in Saudi Arabia and to examine its correlation with various demographic factors. Data from 1,127 employed individuals were collected through an online survey. Descriptive analysis was used to compare the levels of financial literacy, while chi-square tests and regression analysis were employed to determine the impact of demographic factors. The results indicated that working adults in Saudi Arabia have satisfactory financial knowledge, particularly concerning gender, age, education, and the field of study. These demographic factors had a significant relationship with financial literacy. However, weaker connections were observed between financial literacy, living conditions, marital status, and job sector. This study highlights the importance of collaborative efforts to promote financial education among Saudi Arabian professionals. These findings offer valuable insights for policymakers and stakeholders by improving financial literacy among working adults.